1964-2014: Re-imagining the Afri-Caribbean Diaspora: Conversations on the role of place in knowledge construction for Trinbagonians to Brooklyn, New York - Kimeka Campbell (Adult Education Research Conference, 2014)
This paper uses cultural historical activity theory to examine interview and graphic information systems (GIS) data to discuss the role of place in translocal experiences among Trinbagonian migrants in Brooklyn, New York. Migrants largely depend on the knowledge traditions and cultural significance of traditional activities borne out of cultural historical struggle in Trinidad and Tobago. Migrants preserve culture and learn to navigate and remake place in translocal movement to Brooklyn New York through cultural historical underpinnings.